Uterine Leiomyosarcoma (uLMS): A Malignancy in Disguise (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Uterine leiomyosarcoma mimics leiomyoma of the uterus clinically and on ultrasound imaging. The clinical course and prognosis are however markedly different .The entity may commonly present as a pelvic recurrence after initial surgery for unsuspected leiomyosarcoma. The rarity of this clinical entity renders pre-operative diagnosis to be often missed. The staging of this uncommon variant is significantly influenced by the histopathologic diagnosis. Preoperative suspicion and relevant imaging is needed to improve diagnosis and thereby prognosis through proper surgical staging/sampling and optimal surgical resection as there are no specific tumour biomarkers yet. This is a case report depicting prospectively the outcome of a post-menopausal woman who underwent Total abdominal hysterectomy and bilateral salpingo-oophorectomy for a large fibroid which was confirmed histopathologically as Uterine Leiomyosarcoma( uLMS). After the histologic confirmation of uLMS, the patient was advised Combination chemotherapy, but she declined the adjuvant treatment. After 4 months of primary surgery with no initiation of Chemotherapy , she developed pelvic recurrence with invasion of bladder as detected by CT scan. The patient received 3 cycles of palliative combination Chemotherapy with Inj. Doxorubicin , Inj. Ifosfamide and Inj. Mesna ,Inj. Neukine after the detection of recurrence. She sadly succumbed a few days after completion of the third cycle of chemotherapy. This case report highlights the necessity to suspect the possibility of leiomyosarcoma in a post –menopausal lady with fibroid presenting for surgical management.Bangladesh J Obstet Gynaecol, 2021; Vol. 36(1): 69-73